PENGARUH ZAT PENGATUR TUMBUH TRIAKONTANOL DAN JARAK TANAM TERHADAP PERTUMBUHAN TANAMAN TEMBAKAU (Nicotiana tabacum L.) KULTIVAR NANI - Bayu Adji Purwoko; Cucu Suherman; Yudithia Maxiselly (Jurnal Agroekoteknologi, 2017)
Tobacco plant (Nicotiana tabacum L.) is an estate crop commodity that play an important role as a source of farmers and state income. The production of tobacco Cultivar Nani is categorized as low. The cultivation technique is not optimalized by the average of tobacco farmers was the factor. In consequence, cultivation technique improvement is required. Optimization of plant spacing and plant growth regulator triacontanol treatment are believed as a way to increase tobacco’s production along with the increase of plant growth. The purpose of this research was to find out the interaction between plant growth regulator triacontanol treatment and plant spacing on growth of tobacco Cultivar Nani. This experiment was conducted from January until June 2017 at the Ciparanje Experimental Station Faculty of Agriculture, Universitas Padjadjaran, Jatinangor, Sumedang, Province of West Java. This experiment was conducted using a split plot design with two factors and three replications. Plant spacing treatment as main plot was consisted of three level treatments that is 30 cm x 80 cm, 40 cm x 80 cm, and 50 cm x 100 cm. Plant growth regulator triacontanol as sub plot was consisted of four levels treatments that is 0 ppm, 500 ppm, 1000 ppm and 2000 ppm. The result of this experiment showed that there was interaction between triacontanol treatment and plant spacing in chlorophyll content of tobacco’s leaf. Plant spacing 30 cm x 80 cm was significant in tobacco’s height on 7 weeks after planting. Giving 2000 ppm concentration of triacontanol with 40 cm x 80 cm space generated to highest content of chlorophyll in tobacco’s leaf and efficient seed usage.Keywords: Growth, Plant spacing, Tobacco, Triacontanol